Turnover intention among specialist medical practitioners in sabah: a statewide multicenter cross sectional study - Nafsah Dulajis; Mohd Yusof Ibrahim; Ma Swe; Awang Setia Musleh; Aizuddin Hidrus (Malaysian Public Health Physicians Association, 2022)
Movement of highly skilled physicians from the public sector to the private sector is interrupting progress towards Universal Health Coverage (UHC) and subsequently Sustainable Development Goals (SDG). There is insufficient information to understand factors associated with turnover intention among specialist medical practitioners in Sabah, a state in Malaysia with the least number of clinical specialists for all specialties. This study intended to determine prominent factors affecting turnover intention using a cross sectional study conducted among Ministry of Health’s specialist medical practitioners across Sabah. Respondents were chosen using convenience sampling technique to complete a self-administered questionnaire consisting of sociodemographic information, work characteristics, the 10 item Warr-Cook-Wall (WCW) job satisfaction scale, a question on private sector employment offer and turnover intention. Descriptive and bivariate analyses were used to identify significant factors affecting turnover intention. A total of 101 completed questionnaires were analysed. A total of 75 (74.3%) respondents were younger than 40 years old and 57 (56.4%) of them were male. Almost one third (31.7%) of specialist medical practitioners in Sabah were actively seeking alternative employment. Factors associated with turnover intention were low job satisfaction score (t = 3.516, 95% CI 2.64-9.49, p < 0.005) and career development opportunities (x² = 5.766, p < 0.05). Turnover intention among specialist medical practitioners in Sabah was significantly associated with low job satisfaction and dissatisfaction with career development opportunity. There is a dire need for an effective retention strategy to retain these limited highly skilled health personnel.